A Dynamic and Fully Implicit Non‐Isothermal, Two‐Phase, Two‐Component Pore‐Network Model Coupled to Single‐Phase Free Flow for the Pore‐Scale Description of Evaporation Processes. Issue 4 (26th April 2021) - Weishaupt, K.; Helmig, R.
Abstract: We couple a dynamic, fully implicit non‐isothermal two‐phase, two‐component pore‐network model (PNM) to a free‐flow domain where the single‐phase flow Navier‐Stokes equations with component and energy transport are solved. A monolithic coupling scheme guarantees the conservation of mass, momentum and energy across the coupling interface and allows solving the system without any coupling iterations. We present a numerical example and show that the model is able to temporally resolve the pore‐local flow and transport dynamics of an evaporation process. Key Points: We present a coupled free‐flow/pore‐network model for simulating the pore‐scale dynamics of evaporation processes The dynamic, fully implicit pore‐network model considers phase change and energy transport The monolithic coupling scheme is inherently mass, energy and momentum conservative and does not require any coupling iterations